Testing the Relationship between Financial Inclusion, Institutional Quality and Inclusive Growth for Nigeria - Rahman Olanrewaju Raji (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
This paper examines the causal relationship between financial inclusion, institutional quality and inclusive growth within a four-variate ARDL-EC framework and forecast error variance decomposition technique for the period of 2003-2018 using quarterly data in Nigeria. The paper incorporates two variables to capture institutional quality (government effectiveness and regulatory quality) in order to eliminate variable omission bias in which most existing studies are characterised. Those adopted techniques conﬁrm the long-run and bi-causal relationships mainly between financial inclusion and inclusive growth in Nigeria. In addition, bi-directional causal relationships of the outcome of the study are also established between financial inclusion and government effectiveness, likewise between inclusive growth and regulatory quality mainly in the short-run. The results based on the model and empirical outputs suggest that for the authorities of this economy to achieve and sustain equitable growth, fully disciplined policies that can promote and enhance financial inclusion and inclusive growth of the greater proportion of the population should not be managed and handled by loosed hands This paper examines the causal relationship between financial inclusion, institutional quality and inclusive growth within a four-variate ARDL-EC framework and forecast error variance decomposition technique for the period of 2003-2018 using quarterly data in Nigeria. The paper incorporates two variables to capture institutional quality (government effectiveness and regulatory quality) in order to eliminate variable omission bias in which most existing studies are characterised. Those adopted techniques conﬁrm the long-run and bi-causal relationships mainly between financial inclusion and inclusive growth in Nigeria. In addition, bi-directional causal relationships of the outcome of the study are also established between financial inclusion and government effectiveness, likewise between inclusive growth and regulatory quality mainly in the short-run. The results based on the model and empirical outputs suggest that for the authorities of this economy to achieve and sustain equitable growth, fully disciplined policies that can promote and enhance financial inclusion and inclusive growth of the greater proportion of the population should not be managed and handled by loosed hands